Microencapsulation of ammodaucus leucotrichus essential oil using chitosan/ TPP/vanillin chemical system - Halla, Noureddine (2017)
A. leucotrichus (Coss. & Dur.) Coss. & Dur., known in Algeria as “Kammûnes-sofi”, is a medicinal plant that finds culinary use by indigenous populations. Among others, it is used against stomach pain, indigestion, diarrhea, vomiting, fever, and to combat high blood pressure. In this work, the essential oil of A. leucotrichus, obtained by steam distillation (3h) from fruits collected in March 2015 from Tassili n'Ajjer, a vast plateau in south-east Algeria (25°30'0" N and 9°0'0" E), was chemically and biologically characterized and thereafter microencapsulated using a chitosan/TPP/vanillin system.